Penerapan Implementasi Smart People Pada Era Smartphone Berdasarkan UU No.19 Tahun 2016 atas Perubahan UU No.11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Gatot Efrianto (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2024)
Most people in their lives in the modern era cannot be far from communication tools, where these communication tools are not just for communicating but can be used for other purposes such as browsing the internet, reading e-books, shopping, transferring money, games, and even religious activities. This sophisticated communication tool has capabilities like a computer device, which is more popularly known as a smartphone. The benefits of smartphone devices are that many people use them for their own benefit, but some people often use them to the detriment of other people. The aim of this research is to determine the implementation of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), regarding the principles of benefits and limitations for users of internet-based applications on smartphone devices. This research study has a normative juridical nature as the main approach, considering that the discussion is based on statutory regulations and legal principles that apply in matters of information technology crime. The juridical approach is intended to carry out studies of the legal field, especially criminal law. In its development, the smartphone era has made the Government continue to try to create legal regulations to regulate and limit the use of applications on smartphone devices regarding information and electronic transactions, so that users can wisely use applications on their smartphone devices. The ITE Law is a much-needed legislative product and has become the basis for regulations in the field of information technology utilization and electronic transactions and was born as a constitutional solution from the state to regulate ethics for its users.